Die Krise der VWL und die Vision einer Pluralen Ökonomik - Dirk H. Ehnts; Lino Zeddies (Wirtschaftsdienst, 2016)
Die andauernde Finanzkrise hat tief iegende Probleme des ökonomischen Mainstreams offengelegt und lässt Forderungen nach einer Erneuerung des ökonomischen Denkens lauter werden. Die Autoren beschreiben die Kritik am Status quo und gehen dabei auf die Vorwürfe von Einseitigkeit, blinden Flecken, Realitätsferne und impliziter Normativität ein. Als vielversprechender Gegenentwurf wird die Vision einer Pluralen Ökonomik vorgestellt und anhand von fünf charakteristischen Säulen beschrieben: Theorienpluralismus, Methodenpluralismus, historische Fundierung, wissenschaftstheoretische und ethische Reflexion sowie Interdisziplinarität. – – The lasting turbulences of the Great Financial Crisis (GFC) have exposed deep structural problems with mainstream economics and strengthen the argument for a revolution in economic thinking. This paper describes common criticisms of the status quo with regard to one-sidedness, detachment from reality, blind spots and implicit normativity. Thereby, a distinction is made between different sociological spheres where economics plays a role such as teaching, research and the typical 'economist's voice' in public debate. Causes of the persistence of the status quo are addressed as well. As a promising alternative, the vision of a Pluralist Economics is illustrated and described in terms of five characteristic foundations: Theoretical pluralism, methodological pluralism, historical foundation, epistemological as well as ethical reflection and interdisciplinarity. Finally, a description is given of various activities of the Network for Pluralist Economics, which is committed to this vision of a reinvented economics discipline and which is supported by numerous university groups in German-speaking countries.
Keywords: A14; A20; B50; 330